PENGEMBANGAN LEMBAR KERJA PRAKTIKUM MAHASISWA BERBASIS RISET SOLID LIPID NANOPARTIKEL (SLN) TRIMIRISTIN HASIL ISOLASI BIJI PALA (Myristica fragrans) - Pramesthi Regita Putri; Agus Sundaryono; Hermansyah Amir (University of Bengkulu, 2022)
This research aims to determine the feasibility, practicality, and effectiveness of LKPM based on solid lipid research of trimiristin nanoparticles resulting from nutmeg seed insulation as a guide sheet of organic chemical practicum II in lipid matter. This research uses 4-D methods, consisting of 4 stages, namely define, design, develop, and disseminate. However, in this study the researchers only performed until the third stage which is the development stage (develope). This research data is obtained from the results of material and media expert validation questionnaires, product practicality questionnaires as well as pretest and posttest results tested to fourth semester students who participated in organic chemistry course II.LKPM based on Research Solid Lipid Nanoparticle (SLN) Trimiristin resulting from Nutmeg Seed Isolation that has been developed obtained a value of 83.75% on media validation and obtained a value of 87.3% on material validation, which means it is in the category of highly feasible. While the practicality percentage result of 88.36 % on the small-scale test, which goes into the category strongly agrees, The average result that means students strongly agree that the products that have been developed are very practical to use. The average value of N-Gain Small Scale Test Score is 0.43, meaning it can be concluded that The Student Practicum Worksheet (LKPM) based on Solid Lipid Nanoparticle (SLN) trimiristin research resulting from Nutmeg Seed Isolation (Myristica fragrans) has moderate effectiveness value.